ASME/JSME 2007 Thermal Engineering Heat Transfer Summer Conference, Volume 3 2007
DOI: 10.1115/ht2007-32916
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inlet Flow Conditions on Gas-Liquid Two-Phase Flow in a Micro Tube

Abstract: In the present study, the effects of inlet geometry on the microscale two-phase flow patterns have been examined. The relationships among the flow pattern, the void fraction, the pressure loss and the heat transfer coefficient have been also investigated under different inlet flow conditions. At the inlet, a stainless steel tube is inserted into the micro glass tube, of which inner diameter is 300 and 600 μm. The gas and liquid paths and the diameter of the inner tube are interchangeable. The flow patterns are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…) in micro tubes approaches unity. Serizawa et al (2002), Hayashi et al (2007) and Saisorn and Wongwises (2008) found that the measured void fraction in micro tubes agrees well with the homogeneous void fraction, i.e. slip ratio ≈ 1.…”
Section: Assessment Of Models and Correlationsmentioning
confidence: 59%
“…) in micro tubes approaches unity. Serizawa et al (2002), Hayashi et al (2007) and Saisorn and Wongwises (2008) found that the measured void fraction in micro tubes agrees well with the homogeneous void fraction, i.e. slip ratio ≈ 1.…”
Section: Assessment Of Models and Correlationsmentioning
confidence: 59%
“…5.11 (H)). [54], the present pressure loss measurements at low gas flow rate is found to be matching well with the pressure measurements conducted by Hayashi et al [54] where their measurements were performed at a higher gas flow rate using a similar set up. drop.…”
Section: Estimation Of the Heat Losssupporting
confidence: 90%
“…Flow Visualization and Heat Transfer Measurements of two-phase Flow in Microtubes the pressure drop for the bubbly and slug flows. Conversely, it will overestimate the pressure drop for the churn and annular flows according to the results reported by Hayashi et al[54]. Furthermore,Fig.…”
supporting
confidence: 75%
See 2 more Smart Citations